2019
DOI: 10.1021/acsearthspacechem.9b00235
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic Product Formation in Aqueous Brown Carbon Systems

Abstract: Brown carbon in aerosol remains a significant source of error in global climate modeling due to its complex nature and limited product characterization. Though significant efforts have been made in the previous decade to identify the major lightabsorbing brown carbon chromophores formed through the reactions of carbonylcontaining compounds with ammonium, substantial work is still required to identify the main absorbing species resulting from reactions of glyoxal, glycolaldehyde, and hydroxyacetone with ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(119 citation statements)
references
References 54 publications
7
110
0
2
Order By: Relevance
“…Similar speciation studies using HPLC-MS in MG/AS aerosol mimic solutions also identified m/z peaks consistent with methylated analogues to these heterocyclic products [20,32]. These products have all been observed [20,32] or estimated [18,32] to absorb light in the UV/visible region, classifying these compounds as brown carbon (BrC) species that may contribute to overall aerosol direct forcing effects.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…Similar speciation studies using HPLC-MS in MG/AS aerosol mimic solutions also identified m/z peaks consistent with methylated analogues to these heterocyclic products [20,32]. These products have all been observed [20,32] or estimated [18,32] to absorb light in the UV/visible region, classifying these compounds as brown carbon (BrC) species that may contribute to overall aerosol direct forcing effects.…”
Section: Introductionmentioning
confidence: 60%
“…Glycolaldehyde (GA) and methylglyoxal (MG), which are similarly structured to glyoxal, appear in similar environments, though in smaller quantities [16,17]. GA and MG have been proposed to undergo analogous chemistry to glyoxal in aqueous conditions [18,19]. In addition, MG has also been identified to generate comparable or greater quantities of light-absorbing dark chemistry products compared to G [20,21] and can alter the bulk-phase physical properties of aerosol systems, even in trace amounts [20,22,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Heidi's Ph.D. work involved time-dependent density functional theory (TDDFT), so she was able to design a project in which the student carried out and analyzed TDDFT calculations to determine how reaction products identified by the Galloway lab contribute to absorption of visible light in atmospheric aerosols. [4,5] Likewise, another student wondered if it would be possible to computationally model aspects of the melanopsin protein he began studying in Prof. James Dearworth's biology lab at Lafayette. Heidi used her postdoc experience studying rhodopsin to develop a collaborative QM/MM project investigating the structure of turtle melanopsin.…”
Section: Designing Student Projectsmentioning
confidence: 99%